Epistemological Construction of Ulil Amri in QS. An-Nisa’ 59: A Comparative Study of Tafsir Marah Labid and Tafsir Al-Misbah - Feri Nuryadi; Naqiyah Mukhtar; Fathin Fauzan (ZAD Al-Mufassirin, 2026)
The concept of ulil amri in QS. An-Nisa’ [4]: 59 occupies a significant position in Islamic discourses on authority and obedience, particularly within contemporary Muslim societies where debates concerning the nature and legitimacy of religious authority continue to evolve. This study aims to examine the epistemological construction of ulil amri through a comparative analysis of Tafsir Marah Labid by Nawawi al-Bantani and Tafsir Al-Misbah by M. Quraish Shihab. Employing a qualitative library-based approach and the method of comparative exegesis, the study draws upon primary tafsir sources as well as  relevant scholarly literature on Qur’anic interpretation and Islamic intellectual traditions. The findings reveal that Nawawi al-Bantani embodies a classical Sunni epistemology characterized by an emphasis on textual authority and the hierarchical position of religious scholars, whereas Quraish Shihab represents a contextual and integrative epistemology that accommodates contemporary socio-intellectual realities. The study demonstrates that the epistemological transformation from classical Nusantara exegesis to contemporary Indonesian tafsir has significantly influenced  the construction of religious authority and obedience in modern Muslim societiesAccordingly, this research contributes to a deeper understanding of how epistemological frameworks shape exegetical perspectives and inform evolving conceptions of authority within contemporary Islamic thought.